Semiotic Analysis of Weapon in Mobile Legend Game (Sastra Inggris UNPAM, 2025)
The purpose of this study is to find what signs are used in the weapons of the mobile legend game and analyze the meaning of the signs contained in the weapons of the mobile legend game (2016) into denotation, connotation, and myth meaning. The research method used in this study was a consistent qualitative descriptive approach to identify and analyze several studies through signs in the Mobile Legends game. This study used the theory of semiotics developed by Barthes. The data in the findings and analysis section of the research is taken from the Mobile Legends game. In the results of this study, there were 17 signs that had implied meaning given by the mobile legend game to indicate items from the mobile legend game that described the denotation, connotation, and myth of the signs in the mobile legend game.